Initial Development of the KITABOOKA Platform to Support the Madrasah English Mentoring Program Based on Cultural Literacy and Soft Skills - Jupri Hadi, Marham; Fitriani; Ma'we, Hannatul; Hully; Hakim, Marwan (Bulletin of Network Engineer and Informatics, 2025)
The digital era demands innovation in English language learning that not only focuses on linguistic competence but also integrates cultural literacy and soft skills. Web-based collaborative learning platforms become a solution to create an authentic and interactive learning environment. This study aims to develop the initial KITABOOKA platform as a collaborative English learning medium that integrates cultural literacy and soft skills through a web-based mentoring program using the Research and Development (R&D) ADDIE model. The research uses an R&D approach with the ADDIE model. However, in this study, we only use the first three stages (Analysis, Design, Development). Data were collected through surveys, interviews, and observations from 25 respondents consisting of students, university students, lecturers, and English teachers. Based on the analysis of user needs, this platform needs to be equipped with key features such as a learning module, English language learning activities, cultural literacy features, soft skills enhancement features, digital mentoring system features, and other general supporting features. Additionally, validation by seven experts showed that the initial design of the KITABOOKA platform received an average score of 4.55, categorized as very valid, covering aspects of content, appearance, technical, pedagogical, and usability. The analysis of the needs from users and experts indicates that the KITABOOKA platform already meets the feasibility standards as a collaborative digital learning platform and is ready to proceed to the limited testing phase in the next study.